Whither 'high-tech' labor? Codification and (de-)skilling in automotive components value chains. Issue 99 (February 2019) - Machacek, Erika; Hess, Martin
Abstract: This paper seeks to address the limits of the global value chain (GVC) framework for explaining processes of deskilling in the changing international division of labor, outsourcing and offshoring. In the GVC framework, deskilling is insufficiently addressed in the context of social upgrading which usually focuses on measureable labor standards and enabling rights. Using a case study of component manufacturing in the automotive sector, this study shows that a critical understanding of the codification process is key for identifying how deskilling occurs within international divisions of labor in a high-tech industry. The paper draws on Michael Polanyi's conceptualization of tacit knowledge and Harry Braverman's work on labor and monopoly capital to refine and frame the role of codification in GVC governance structures. Currently, explanations of the ability to codify knowledge center on a technical and, at most, implicit experiential dimension of tacit knowledge (the know-how acquired through experience), and thus only on one of two constituents of Polanyi's conceptualization. Yet the cognitive dimension, which relies on the articulation and sharing of experiences, imitation, performance and other forms of knowledge exchange among workers, is largely absent. This is detrimental to explaining the complex processes of deskilling within GVCs. Empirically, our argument is illustrated by analyzing intra-firm decisions on codifying information for the manufacturing of automotive magnet components in Europe and in the magnet industry hub of Ningbo, China. Specifically, we discuss how these decisions liberate some workers in some places for skill upgrading (upskilling), but are clearly limiting many others to perform routine tasks removed from any innovative collaboration, i.e. (relative) deskilling. The paper finds an international division of labor facilitated and maintained to no small extent by intra-firm decision-making on knowledge codification, with mixed results for skills upgrading and (relative) deskilling.